Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/v11121133
|View full text |Cite
|
Sign up to set email alerts
|

Camelids and Cattle Are Dead-End Hosts for Peste-des-Petits-Ruminants Virus

Abstract: Peste-des-petits-ruminants virus (PPRV) causes a severe respiratory disease in small ruminants. The possible impact of different atypical host species in the spread and planed worldwide eradication of PPRV remains to be clarified. Recent transmission trials with the virulent PPRV lineage IV (LIV)-strain Kurdistan/2011 revealed that pigs and wild boar are possible sources of PPRV-infection. We therefore investigated the role of cattle, llamas, alpacas, and dromedary camels in transmission trials using the Kurdi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 66 publications
2
22
1
Order By: Relevance
“…The univariable finding that cattle introduction to the compound increases household herd FOI may result from cattle introductions occurring at the same time as sheep or goat introductions (which may be PPRV infected and shedding virus). This finding is counter balanced by the univariable evidence presented in this study that grazing cattle with sheep and goats was associated with a significantly lower household herd FOI compared to when cattle are separated, and is consistent with the prevailing dogma and experimental transmission findings [44,45] that cattle are likely dead-end PPRV hosts. However, the exact role of cattle in transmitting PPRV is still under experimental investigation [44,45].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The univariable finding that cattle introduction to the compound increases household herd FOI may result from cattle introductions occurring at the same time as sheep or goat introductions (which may be PPRV infected and shedding virus). This finding is counter balanced by the univariable evidence presented in this study that grazing cattle with sheep and goats was associated with a significantly lower household herd FOI compared to when cattle are separated, and is consistent with the prevailing dogma and experimental transmission findings [44,45] that cattle are likely dead-end PPRV hosts. However, the exact role of cattle in transmitting PPRV is still under experimental investigation [44,45].…”
Section: Discussionsupporting
confidence: 79%
“…This finding is counter balanced by the univariable evidence presented in this study that grazing cattle with sheep and goats was associated with a significantly lower household herd FOI compared to when cattle are separated, and is consistent with the prevailing dogma and experimental transmission findings [44,45] that cattle are likely dead-end PPRV hosts. However, the exact role of cattle in transmitting PPRV is still under experimental investigation [44,45]. Multivariable analysis revealed that goat and sheep, but not cattle, introduction was a significant production practice associated with increased PPRV seroconversion.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Lastly, we previously discussed the role of cattle in PPRV transmission in [19]. Two recent experimental transmission trials involving cattle did not find onward transmission from cattle [48,49]. This is an active area of research, as variation due to the use of local vs. non-local breeds and the choice of PPRV isolate may impact the results.…”
Section: Discussionmentioning
confidence: 99%
“…Their role in natural systems needs further consideration (27). Multiple reports suggest that dromedaries (Camelus dromedarius) are susceptible to PPRV infection and express disease clinically, as observed in Iran, Ethiopia, and Sudan (28-30), though recent PPRV experimental infection trials with camelids resulted in no clinical disease or shedding of PPRV (31). Meeting participants discussed the potential of roe deer (Capreolus capreolus) and wild boar facilitating the introduction and spread of PPRV into the European Union, though there is no evidence to suggest that this has occurred.…”
Section: Recent Scientific Insights On Ppr At the Wildlife-livestock mentioning
confidence: 99%